Teacher autonomy in the age of performance-based accountability: A review based on teaching profession regulatory models (2017-2020) - Parcerisa, Lluís; Verger, Antoni; Pagès, Marcel; Browes, Natalie (Education Policy Analysis Archives, 2022)
In recent decades, the governance of educational systems has experienced dramatic changes in many countries. Schools have been given more autonomy whilst being held increasingly accountable at the central level through standardized testing and other forms of external evaluation. The mechanisms of performance-based accountability (PBA) and the consequences attached to test results vary. In high-stakes systems, teachers’ careers are more directly connected to students’ performance, and low performing schools might risk closure, whereas in lower-stakes systems, the official administrative consequences of accountability for school actors are more symbolic than material. The main aim of this paper is to understand the impact of different forms of PBA on teachers’ work from a comparative perspective. Most research on this topic is based on single-context case studies, which makes it difficult to understand the impact of policy factors and professional contexts in teachers’ decisions and autonomy. To address this challenge, we review recent investigations (2017-2020) on the topic and compare their findings in different teachers' regulatory contexts. The review includes 101 articles from the SCOPUS and Web of Science databases. We find that evidence on the impact of PBA on teachers’ perceptions and beliefs are variegated, and that the implications of PBA on teachers’ autonomy does not only depend on the level of accountability stakes, but on teachers’ professional regulation.